Porcine derived relaxin stimulates new vessel formation and improves the disturbed wound healing of the genetically diabetic mice - Squadrito, Francesco; Bitto, Alessandra; Irrera, Natasha; Minutoli, Letteria; Caccia, Paolo; Altavilla, Domenica (Italian Journal of Anatomy and Embryology, 2014)
Diabetic mice are characterized by an altered expression pattern of VEGF, and impaired vasculogenesis during healing. We investigated the effects of porcine derived relaxin in diabetes-related wound healing defects in genetically diabetic mice. An incisional wound model was produced on the back of female diabetic C57BL/KsJm+/+ Leptdb (db+/db+) mice and their normal littermates (db+/+m). Animals were treated daily with RLX (25μg mouse/day subcutaneously) or its vehicle. Mice were killed on days 3, 6 and 12 after skin injury for measurements of vascular-endothelial-growth-factor (VEGF) mRNA and protein synthesis. Furthermore, we evaluated wound-breaking strength, histological changes, and angiogenesis at day 12. At day 6, RLX administration resulted in an increase in VEGF mRNA expression and protein wound content. Furthermore the histological evaluation indicated that RLX improved the impaired wound healing, and increased wound breaking strength at day 12 in diabetic mice. Immunohistochemistry showed that RLX in diabetic animals augmented new vessel formation. These data strongly suggest that RLX may have a potential application in diabetes-related wound disorders.